Performance Assessment Instrument Model in Defensive Lob Learning for Elementary School Students - Hambali, Burhan; Hidayat, Yusuf; Yudiana, Yunyun; Juliantine, Tite; Rahmat, Alit; Gumilar, Agus; Nugraha, Reshandi (Prodi PGSD Penjas FPOK UPI, 2021)
The study was aimed at developing a performance assessment instrument model for defensive lob learning. The research method used was Research Development method for developing an assessment instrument referring to eight stages of activity, including choosing good test criteria, analyzing the sport to be tested, selecting and looking for theoretical concept literatures, selecting test items, establishing procedures, administering expert judgements, testing the instrument, and testing the estimated level of validity and reliability. The participants involved were fifth grade elementary school students aged 11-12 years. The development of instrument referred to a performance test instrument with an individual performance assessment model. The analysis consisted of the estimation of content validity (Lawshe's CVR), test-retest reliability, and inter-rater reliability (interclass coefficient correlation). The results of the analysis showed that the reliability and validity of the assessment instrument obtained a good criteria significantly (p_value 0.05). The results of reliability and validity testing conclude that the developed performance assessment instrument model can be used to measure defensive lob skills in Badminton learning for Elementary School students.